Benefits and risks of shared services in healthcare. Issue 3 (16th May 2016) - Kennewell, Suzanne; Baker, Laura
Abstract : Purpose: – The purpose of this paper is to explore the experiences of staff in a large, public health service involved in transitioning support services to a shared services model. It aims to understand their perceptions of the benefits and risks arising from this change. Design/methodology/approach: – Thematic analysis of qualitative data from semi-structured interviews with both service provider and customer agency staff was used to identify, analyze and report patterns of benefits and risks within data. Findings: – Staff expressed the need for relevant subject-matter-experts to work within customer agencies to facilitate effective communication between the customer agency and shared services provider, reflecting observations found in out-sourcing literature. Research limitations/implications: – Results point to significant challenges continuing to occur for shared services in healthcare. Risks identified suggest a more intimate relationship between clinical and support services than previously discussed. Originality/value: – Previous discussion of the shared services model has not considered the skills, knowledge and ability required by staff in the customer agency. This research indicates that in the absence of such consideration, the concepts of the shared services model are weakened.